2023
DOI: 10.1002/nag.3513
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale failure prediction of clay rock from small‐scale damage mechanisms of the rock medium using multiscale modelling

Abstract: Clay rocks are multiphase porous media whose complex structure is characterised by heterogeneity and possible anisotropy on a wide range of scales. The mesoscopic scale plays a particular role in deformation mechanisms under mechanical loading by cracking. The behaviour of rocks at mesoscale is characterised by the material and morphological (shape and size) properties of its components and their interactions. The accurate reproduction and influence of these mesoscale characteristics on the material behaviour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…For pi>1.5σ0,${p_i} > 1.5{\sigma _0},$ the influence of the VE is already visible as the εVM${\varepsilon _{VM}}$ maps start to be slightly different; and for pi3.5σ0${p_i} \ge 3.5{\sigma _0}$, strains are localized and as soon as pi4.5σ0${p_i} \ge 4.5{\sigma _0}$, quasi‐periodic SBs are observed in R22‐simu‐b case while conjugated SBs are found in other cases ( R02‐simu‐b and R50‐simu‐b ). These two modes of strain localization (conjugated and quasi‐periodic) solutions shown are well consistent with other numerical and experimental observations on the borehole failure 18,49–52 …”
Section: Variability and Non‐uniqueness Of Numerical Solutions In Enh...supporting
confidence: 90%
“…For pi>1.5σ0,${p_i} > 1.5{\sigma _0},$ the influence of the VE is already visible as the εVM${\varepsilon _{VM}}$ maps start to be slightly different; and for pi3.5σ0${p_i} \ge 3.5{\sigma _0}$, strains are localized and as soon as pi4.5σ0${p_i} \ge 4.5{\sigma _0}$, quasi‐periodic SBs are observed in R22‐simu‐b case while conjugated SBs are found in other cases ( R02‐simu‐b and R50‐simu‐b ). These two modes of strain localization (conjugated and quasi‐periodic) solutions shown are well consistent with other numerical and experimental observations on the borehole failure 18,49–52 …”
Section: Variability and Non‐uniqueness Of Numerical Solutions In Enh...supporting
confidence: 90%
“…On the numerical modeling side, a few studies have reported this pre-peak localization. In the context of modeling in a continuous medium, it is generally observed if a slight material heterogeneity has been introduced into the medium [21,44]. It is also observed in the context of discrete medium modeling [14].…”
Section: Alternative Models and Elastic Sensitivitymentioning
confidence: 99%
“…Considering the complex mesostructure of clay rocks, one possibility to evaluate their impacts on mesoscale and macroscale overall mechanical responses is to use a multi‐scale approach. Such approach allows to study a statistically equivalent Representative Elementary Volume (REV for 3D case) or Representative Elementary Area (REA for 2D case) to determine the behaviour of the equivalent homogeneous medium 24–33 . In particular, computational homogenisation methods, 34–36 also known as multi‐scale analyses, have emerged.…”
Section: Introductionmentioning
confidence: 99%
“…Such approach allows to study a statistically equivalent Representative Elementary Volume (REV for 3D case) or Representative Elementary Area (REA for 2D case) to determine the behaviour of the equivalent homogeneous medium. [24][25][26][27][28][29][30][31][32][33] In particular, computational homogenisation methods, [34][35][36] also known as multi-scale analyses, have emerged. They include, among others, finite element squared (FE 2 ) 24,[37][38][39][40] and FEM-DEM 41 methods for continuous media at the large scale and heterogeneous/discrete material at the small scale.…”
Section: Introductionmentioning
confidence: 99%